2020
DOI: 10.1089/heq.2020.0048
|View full text |Cite
|
Sign up to set email alerts
|

Association of Compensation and Educational Debt with Burnout and Perceived Impact of Debt on Women Physicians' Career and Lifestyle Choices

Abstract: This study investigated the magnitude and consequences of educational debt for women physicians. Methods: Participants in a women's leadership course were surveyed. Results: Of the 185 U.S. physician respondents, 152 (82%) and 85 (46%) reported past debt and current debt, respectively. A total of 164 (89%) perceived a relationship between financial stress and burnout, although burnout scores did not vary by debt magnitude. One-fifth or more reported a negative past influence of debt on each of nine aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…[49][50][51] These studies support the idea that burnout may not be solely related to sex/gender but that this observed association may be confounded by other factors. 49,51,52 Finally, practice setting (academic vs. private) and clinical area of focus were not associated with burnout in board-certified physiatrists, 10 and similar findings were seen in this study as planned practice setting or plans to pursue fellowship did not show significant associations with burnout in PM&R residents.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[49][50][51] These studies support the idea that burnout may not be solely related to sex/gender but that this observed association may be confounded by other factors. 49,51,52 Finally, practice setting (academic vs. private) and clinical area of focus were not associated with burnout in board-certified physiatrists, 10 and similar findings were seen in this study as planned practice setting or plans to pursue fellowship did not show significant associations with burnout in PM&R residents.…”
Section: Discussionsupporting
confidence: 80%
“…A recent study that looked at US women attending physicians in PM&R also found that hours worked per week was significantly associated with burnout scores, 49 and several studies have shown that educational debt is higher in women and may contribute to burnout 49–51 . These studies support the idea that burnout may not be solely related to sex/gender but that this observed association may be confounded by other factors 49,51,52 . Finally, practice setting (academic vs. private) and clinical area of focus were not associated with burnout in board-certified physiatrists, 10 and similar findings were seen in this study as planned practice setting or plans to pursue fellowship did not show significant associations with burnout in PM&R residents.…”
Section: Discussionmentioning
confidence: 62%
“…One hundred and fifty-five respondents (42.1%) indicated they were experiencing burnout symptoms on the MZBS. Our group had significantly less burnout (P < .0001) compared to a study of women physicians, the majority of whom were mothers, that found burnout in 64.9% of those surveyed using a similar question and 5-point response scale to the MZBS (Larson, et al, 2020). One hundred and twenty-two respondents (33.1%) fit the HLS criteria, but no difference was found in burnout scores between this subgroup and others (P = .37).…”
Section: Resultscontrasting
confidence: 51%
“…In this group of women attending physicians who self-identify as runners, we found a reduced prevalence of burnout compared to a similar cohort of attending women physicians at a leadership conference. 14 Increased fruit and vegetable consumption was associated with increased time exercising per week. We observed a trend of lower burnout with increased exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation